Kombinasi Modalitas Elektroterapi dan Latihan Terapeutik pada Post-Operatif Ruptur Tendon Achilles Sinistra: Studi Kasus di Praktik Fisioterapi Murjito, M.Kes - Nanda Salsabila Putri Wibowo; Chelsea Farrel Anindya; Ali Multazzam; Murjito Murjito (Lembaga Pengembangan Kinerja Dosen, 2026)
Achilles tendon rupture is a common lower extremity injury that significantly affects functional mobility and gait performance. Post-operative patients frequently experience pain, edema, limited range of motion (ROM), muscle weakness, and impaired ambulation. Physiotherapy rehabilitation plays a crucial role in restoring tissue integrity and functional capacity. This case study aimed to analyze the effectiveness of combined electrotherapy modalities and therapeutic exercises in a post-operative left Achilles tendon rupture patient. The intervention included ultrasound therapy, Transcutaneous Electrical Nerve Stimulation (TENS), infrared therapy, dry needling combined with Percutaneous Electrical Nerve Stimulation (PENS), and progressive therapeutic exercises such as isometric training and calf raises. Clinical outcomes were evaluated through ROM measurement, Manual Muscle Testing (MMT), edema observation, and gait analysis across four therapy sessions. Results demonstrated gradual improvement in dorsiflexion and plantarflexion ROM, reduction of edema, increased gastrocnemius-soleus muscle strength, and restoration of independent ambulation without assistive devices. The multimodal physiotherapy approach appears to support tendon healing, enhance neuromuscular activation, and accelerate functional recovery during the subacute post-operative phase.